2019
DOI: 10.1002/ccr3.2277
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a massive naproxen overdose with therapeutic plasma exchange in a dog

Abstract: In comparison with other over‐the‐counter anti‐inflammatory drugs, naproxen has a longer half‐life in dogs and can lead to severe morbidity and mortality. This report describes the successful use of membrane‐based therapeutic plasma exchange after a massive ingestion of naproxen by a dog resulting in 86% reduction in plasma concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Ibuprofen has greater potential for morbidity in dogs compared with other NSAIDs, 1 , 12 , 16 , 21 , 29 , 30 while the nonselective nature of naproxen and its long half‐life of 74 hours has been highlighted throughout the literature as a cause for concern. 1 , 14 , 16 , 31 Our study found that ibuprofen toxicosis was associated with the development of more severe clinical signs compared carprofen but not naproxen. Similarly, others have not identified a significant difference between ibuprofen and naproxen toxicosis with regards to the development of AKI or signs of GI disease in dogs undergoing TPE.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…Ibuprofen has greater potential for morbidity in dogs compared with other NSAIDs, 1 , 12 , 16 , 21 , 29 , 30 while the nonselective nature of naproxen and its long half‐life of 74 hours has been highlighted throughout the literature as a cause for concern. 1 , 14 , 16 , 31 Our study found that ibuprofen toxicosis was associated with the development of more severe clinical signs compared carprofen but not naproxen. Similarly, others have not identified a significant difference between ibuprofen and naproxen toxicosis with regards to the development of AKI or signs of GI disease in dogs undergoing TPE.…”
Section: Discussionmentioning
confidence: 62%
“…Ibuprofen has greater potential for morbidity in dogs compared with other NSAIDs, 1,12,16,21,29,30 while the nonselective nature of naproxen and its long half-life of 74 hours has been highlighted throughout the literature as a cause for concern. 1,14,16,31 Our study found that ibuprofen toxicosis was associated with the development of more severe clinical signs compared carprofen but not naproxen.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…In severe recent (<12 hours) NSAID intoxications in which renal and central nervous system (CNS)impairment is expected or observed, therapeutic plasma exchange (available at some referral centres) should be considered as early as possible. This has been shown to be effective at reducing the levels of circulating ibuprofen (Walton and others 2017a), meloxicam (Walton and others 2017b), carprofen (Kjaergaard and others 2018) and naproxen (Kicera‐Temple and others 2019), and there is growing support for its use in severe NSAID intoxications (Rosenthal and Labato 2019).…”
Section: Common Toxicants Affecting the Gastrointestinal Systemmentioning
confidence: 99%